2018
DOI: 10.1177/2325967118764884
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Return to Sport After Revision Anterior Cruciate Ligament Reconstruction in Adolescent Athletes

Abstract: Background:The number of adolescent anterior cruciate ligament (ACL) injuries is rising with increased participation in higher level athletics at earlier ages. With an increasing number of primary ACL reconstructions (ACLRs) comes a rise in the incidence of revision ACLRs.Purpose:To evaluate the clinical results of revision ACLR across a group of high-level adolescent athletes with at least 2-year follow-up.Study Design:Case series; Level of evidence, 4.Methods:A retrospective review of 21 adolescent athletes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 26 publications
2
39
0
Order By: Relevance
“…This range of variability is consistent with data published for ACL reconstruction and not as high as in some series reporting outcomes of ACLR in young athletes participating in pivoting sports. [58][59][60] Comparative studies only reported graft rupture rates at shorter durations of follow-up. Although it is promising to note a lack of significant difference in graft rupture rates in the comparative studies, they were associated with a high risk of bias with respect to MINORS criteria and specific limitations included a lack of randomization, a small study population, and an absence of a sample size 50 and Henle et al, 36 do not report the rehabilitation protocol followed.…”
Section: Discussionmentioning
confidence: 99%
“…This range of variability is consistent with data published for ACL reconstruction and not as high as in some series reporting outcomes of ACLR in young athletes participating in pivoting sports. [58][59][60] Comparative studies only reported graft rupture rates at shorter durations of follow-up. Although it is promising to note a lack of significant difference in graft rupture rates in the comparative studies, they were associated with a high risk of bias with respect to MINORS criteria and specific limitations included a lack of randomization, a small study population, and an absence of a sample size 50 and Henle et al, 36 do not report the rehabilitation protocol followed.…”
Section: Discussionmentioning
confidence: 99%
“…The review is however limited by the availability of only 4 studies in competitive athletes and only two studies with larger (> 100) patient numbers. A more recent study has also shown higher return to competitive sport rates (68%) after revision reconstruction in adolescent athletes [9].…”
Section: Return To Sport Ratesmentioning
confidence: 99%
“…Recent studies have reported that isolated ACL reconstructions in pediatric athletes have a 10% to 25% graft re-rupture rate, with less than 70% of patients reported to return to sport. 12,[17][18][19][20] In addition, patients with generalized hypermobility and increased heel height/knee hyperextension have reported high ACL reinjury rates. [21][22][23] Recent systematic reviews have reported that extra-articular procedures reduce knee instability observed on the pivot shift maneuver and subsequently decrease the forces on the ACL graft.…”
Section: Discussionmentioning
confidence: 99%